Homeobox protein B6 and homeobox protein B8 control immune-cancer cell interactions in pancreatic cancer - Bertonnier-Brouty, Ludivine; Bsharat, Sara; Achanta, Kavya; Andersson, Jonas; Pranomphon, Thanya; Singh, Tania; Kaprio, Tuomas; Hagström, Jaana; Haglund, Caj; Seppänen, Hanna; Prasad, Rashmi B.; Artner, Isabella (Springer, 2026)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer lacking effective drugs and therefore new treatment targets are needed. In this study, we define the role of homeobox protein B6 (HOXB6) and HOXB8 in controlling pancreatic cancer tumorigenesis and immune response. Transcriptomic analysis comparing human embryonic and PDAC tissue identified a large overlap of expression profiles suggesting a re-initiation of developmental programs in pancreatic cancer. Specifically, we identified the transcription factors HOXB6 and HOXB8 as potential regulators in PDAC. We described their functions in pancreatic cancer by performing transcriptomic and tumor tissue microarray analyses, in vitro assays in pancreatic and lung cancer cell lines and co-culture experiments with immune cells. Loss of HOXB6 and HOXB8 in pancreatic cancer cells inhibited cell proliferation, induced apoptosis and senescence and enhanced gemcitabine sensitivity. Moreover, reduced HOXB6 and HOXB8 expression in pancreatic and lung adenocarcinoma cell lines affected transcription of immune response pathways which resulted in an increased sensitivity of cancer cells to anti-tumorigenic activities of macrophages suggesting that the HOXB6 and HOXB8 immune regulatory function is conserved in different cancer types. Additionally, naïve M0 macrophages exposed to HOXB8 deficient PDAC cells were unable to differentiate into tumor-associated macrophages, suggesting that HOXB8 promotes the transition of initial anti-tumor macrophage to a tumor-promoting macrophage phenotype in pancreatic cancer. Our findings indicate that HOXB6 and HOXB8 play important roles in regulating cell proliferation, immune response, and treatment resistance to promote pancreatic cancer tumorigenesis and could be useful therapeutic targets.